Comparative analysis of the nutritional, medicinal, and sun protection properties of almond (Prunus dulcis) and tropical almond (Terminalia catappa) nuts. - Panditharathna, G. M.; DewageDona, D. H. D.; Rajapakse, C. S. K. (Food Science and Applied Biotechnology, 2025)
This study compares the nutritional, pharmaceutical, and photoprotective properties of methanolic extracts of Terminalia catappa (TC) and Prunus dulcis (PD) nuts. Phytochemical screening revealed both are rich in bioactive compounds. TC had higher moisture content (11.8%) than PD (3.40%), while other nutritional parameters showed minimal differences. PD exhibited stronger antioxidant activity (DPPH IC50: 78.55 ± 5.10 μg.ml-1; ABTS IC50: 57.19 ± 0.32 μg.ml-1) than TC (DPPH IC50: 89.22 ± 4.40 μg.ml-1; ABTS IC50: 74.36 ± 3.34 μg.ml-1), but TC had a higher FRAP value (41.6 ± 0.23 mg PFE.g-1) than PD (39.15 ± 0.21 mg PFE.g-1). PD showed greater phenolic (199.00 ± 14.65 mg GAE. g-1) and flavonoid (4.78 ± 0.077 mg QE. g-1) contents. TC demonstrated stronger α-amylase inhibition (IC50: 113.40 ± 1.56 μg.ml-1), while PD had better anti-lipase activity. Both exhibited moderate UV-B protection (SPF: 14.52 for TC, 12.92 for PD). These findings highlight TC as a promising alternative for functional foods, cosmeceuticals, and medicinal applications.
Keywords: antioxidant; anti-diabetic; anti-lipase; photoprotective